2002
DOI: 10.1007/s00421-002-0601-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygenation mitigates focal cerebral injury and reduces striatal dopamine release in a rat model of transient middle cerebral artery occlusion

Abstract: The usefulness of the administration of hyperbaric oxygen (HBO) in the treatment of acute focal cerebral ischemia remains debatable. A significant association exists between focal cerebral injury and an excessive release of extracellular dopamine (DA). In vivo microdialysis was used in the present study to examine the effect of HBO on DA release in the striatum during ischemia and reperfusion in rats. The histological changes occurring were also evaluated. Focal cerebral ischemia was induced by occlusion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
(58 reference statements)
3
30
0
5
Order By: Relevance
“…Decreased neuronal shrinkage and edema as well as decreased necrotic damage have been described histologically in animals treated with HBO after ischemia [8, 10, 11, 13]. Also, recent studies have shown a nearly immediate protective effect on apparent diffusion coefficient on HBO treated rats during cerebral ischemia.…”
Section: Mechanism Of Action Of Hbomentioning
confidence: 92%
See 2 more Smart Citations
“…Decreased neuronal shrinkage and edema as well as decreased necrotic damage have been described histologically in animals treated with HBO after ischemia [8, 10, 11, 13]. Also, recent studies have shown a nearly immediate protective effect on apparent diffusion coefficient on HBO treated rats during cerebral ischemia.…”
Section: Mechanism Of Action Of Hbomentioning
confidence: 92%
“…Timing of temporary occlusions ranged from 20 min [11] to 24 h [59]. Several studies used a model involving very early institution of HBO therapy, starting treatment immediately [7, 10, 11, 17 ]or within minutes [6, 14, 62, 67, 68 ]of ischemia. Improved survival, smaller infarct size, and better neurologic function were seen in the HBO-treated animals.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved survival, function and behavior in HBO treated animals were also reported (2,3,5,6,9,10,11,13,14,15,16,17,18,19). Several of the studies used a model involving the nearly immediate institution of HBO, starting treatment immediately (2,9,13,20) or within minutes (8,11,12,14) of ischemia. In models more consistent with conditions in a clinical setting, however, HBO delayed until several hours after the beginning of ischemia was also been shown to be effective.…”
Section: Hyperbaric Oxygen For Stroke Protocol Backgroundmentioning
confidence: 88%
“…Decreased neuronal shrinkage and edema as well as decreased necrotic damage have been described histologically in animals treated with HBO after ischemia. (13,19,20,37) Additionally, and perhaps more importantly, far fewer neurons show evidence of having undergone subsequent apoptosis after ischemia in animals treated with HBO. (15,37,38) HBO exposures in the first few minutes or hours after ischemia must, therefore, effect a lasting physiologic change which interrupts the subsequent cell death cascade.…”
Section: Hyperbaric Oxygen For Stroke Protocol Backgroundmentioning
confidence: 99%